Supersonic shear imaging for the diagnosis of liver fibrosis and portal hypertension in liver diseases: a meta-analysis. (2nd January 2018) - Deng, Han; Qi, Xingshun; Zhang, Tiansong; Qi, Xiaolong; Yoshida, Eric M; Guo, Xiaozhong
ABSTRACT: Background and aims : The meta-analysis aimed to summarize the technical success rate of supersonic shear imaging (SSI) and to evaluate the diagnostic performance of liver and spleen stiffness measurement (LSM and SSM) with SSI for the detection of liver fibrosis, portal hypertension, and gastroesophageal varices in liver diseases. Methods : PubMed, EMBASE, and Cochrane Library databases were searched. Technical success rate of SSI was pooled. Area under curve (AUC), sensitivity, and specificity with corresponding 95% confidence interval (CI) were calculated. Results : Included studies regarding the diagnostic performance of SSI for liver fibrosis, portal hypertension, and esophageal varices numbered 28, 4, and 4 respectively. The pooled technical success rates of LSM and SSM were 95.3% and 75.5%, respectively. The AUC, sensitivity, and specificity of LSM/SSM for different stages of liver fibrosis were 0.85–0.94, 0.7–0.89, and 0.82–0.92, respectively. The AUC, sensitivity, and specificity of LSM were 0.84 (95%CI = 0.8–0.86), 0.79 (95%CI = 0.7–0.85), and 0.82 (95%CI = 0.72–0.88) for clinically significant portal hypertension, 0.85 (95%CI = 0.82–0.88), 0.8 (95%CI = 0.68–0.88), and 0.8 (95%CI = 0.6–0.92) for any varices, and 0.86 (95%CI = 0.83–0.89), 0.86 (95%CI = 0.76–0.92), and 0.61 (95%CI = 0.35–0.83) for high-risk varices, respectively. Conclusions : LSM with SSI had a high diagnostic accuracy for liver fibrosis, but a moderate diagnostic accuracy for portal hypertension and esophageal varices.